Socio-economic segregation in European capital cities: East meets West, toimittaneet Tiit Tammaru, Szymon Marcinczak, Maarten van Ham ja Sako Musterd. London and New York, Routledge, 2016. 389 s. - Rasinkangas Jarkko (Siirtolaisuusinstituutti, 2022)
Kirja-arvio: Socio-economic segregation in European capital cities: East meets West, toimittaneet Tiit Tammaru, Szymon Marcinczak, Maarten van Ham ja Sako Musterd. London and New York, Routledge, 2016. 389 s.